DEVELOPMENT OF A WEB-BASED FINANCIAL RECAPITULATION APPLICATION USING PHP AND MYSQL: A CASE STUDY AT D’AMORE CAFÉ - Munirotusaidah, Siti; Mulyana, Iwan; Rusmansyah, Iyus; Lisnawati, Tuti (LPPM AMIK CBI Sukabumi, 2025)
D’Amore Café is a micro-scale culinary business that previously relied on manual financial recording methods, such as handwritten ledgers and spreadsheets (Rizal et al., 2021). This approach was prone to human error, reporting delays, and difficulties in real-time financial monitoring (Suryani & Suharsono, 2020). To address these issues, a web-based financial application was developed to automatically record, store, and display structured financial data in an accessible way for non-technical users. Built using PHP, JavaScript, MySQL, the system followed the Waterfall model, including planning, analysis, design, implementation, testing, and maintenance (Kumar & Bhatia, 2019). Features include inputting expenses, importing revenue data from Excel, generating reports, calculating balances, and printing outputs. Results showed improved operational efficiency by up to 60%, faster daily/weekly reporting, and more accurate access to financial data. User testing confirmed its intuitiveness and effectiveness for MSMEs without technical skills (Praditha & Wibowo, 2022). The system also enhances data security, accuracy, and transparency in financial management. For future development, mobile compatibility, cloud integration, and advanced analytics are recommended to support scalability (Wibowo et al., 2023). This digital solution enables better cash flow management and strategic planning for small business owners, helping them make informed decisions based on reliable financial insights.